2023
DOI: 10.1001/jamanetworkopen.2023.30327
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Associated Inequities in Acute Myocardial Infarction Treatment and Outcomes

Laurent G. Glance,
Karen E. Joynt Maddox,
Jingjing Shang
et al.

Abstract: ImportanceThe COVID-19 pandemic disrupted usual care for emergent conditions, such as acute myocardial infarction (AMI). Understanding whether Black and Hispanic individuals experiencing AMI had greater increases in poor outcomes compared with White individuals during the pandemic has important equity implications.ObjectiveTo investigate whether the COVID-19 pandemic was associated with increased disparities in treatment and outcomes among Medicare patients hospitalized with AMI.Design, Setting, and Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The results of our study also lend support to concerns about the pandemic’s impact on AMI, another life-threatening condition, for which prior studies have shown mixed results . We found increased odds of inpatient mortality for non–COVID-19 AMI at urban hospitals throughout the entire pandemic period of 2020 through 2021 and at rural hospitals in those months corresponding to the initial wave of COVID-19 in 2020 and subsequent waves in 2021.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results of our study also lend support to concerns about the pandemic’s impact on AMI, another life-threatening condition, for which prior studies have shown mixed results . We found increased odds of inpatient mortality for non–COVID-19 AMI at urban hospitals throughout the entire pandemic period of 2020 through 2021 and at rural hospitals in those months corresponding to the initial wave of COVID-19 in 2020 and subsequent waves in 2021.…”
Section: Discussionsupporting
confidence: 81%
“…Likewise, reluctance to seek care among patients without STEMI was indicated by a greater reduction in hospitalizations during the COVID-19 lockdown compared with STEMI admissions . System stress is another factor for worse patient outcomes, as a recent study found lower revascularization rates but higher mortality rates for patients without STEMI who were admitted during periods of high hospital COVID-19 burdens …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant mortality increases occurred (OR 1.23 vs. baseline) in the United Kingdom as the occupancy of intensive care beds exceeded 85% (6) and in the United States during peak pandemic weeks (OR 1.37 vs. baseline) (7). Investigators have found effects on mortality during surge for specific conditions as well-for example, an increase in non-ST-elevation myocardial infarction mortality of over 50% (8).…”
mentioning
confidence: 99%
“…In a large-scale American patients presented with NSTEMI (n=1,022,439), the odds of mortality increased by 51% (adjusted odds ratio [aOR], 1.51; 95% confidence interval [CI], 1.29–1.76; p<0.001) and the rate of revascularization decreased by 27% (aOR, 0.73; 95% CI, 0.64–0.83; p<0.001) among patients hospitalized during weeks with a high hospital COVID-19 burden (>30%) versus patients hospitalized prior to the pandemic. 5) …”
mentioning
confidence: 99%